1938, Regia Università di Milano. Oggetto: Razza (Milano University Press, 2025)
The history of the anti-Jewish laws of 1938 and the resulting racist persecution, certainly represented the darkest page of modern Italy. The University of Milan, on the occasion of its centenary of foundation, decided to deal with this terrible story for the first time, promoting an exhibition that documented the application of the so-called Racial laws in the University. The catalogue that is now published, integrated with some sections compared to the original layout, allows us to follow the bureaucratic-administrative stages of the persecution and to evaluate its effects on the women and men who suffered it, whether they were accomplished teachers or assistants at the beginning of their career . The volume is enriched by an in-depth analysis of the attitude of Italian philosophy towards racism, a reconstruction of the responses that Piero Martinetti opposed to the racist census and the text of the Laudatio to Senator Liliana Segre on the occasion of the awarding of her honorary degree in Historical Sciences.